"The next-generation": Long-term reproductive outcome of adults born at a very low birth weight. (January 2018) - Drukker, Lior; Haklai, Ziona; Ben-Yair Schlesinger, Mor; Bas-Lando, Maayan; Gordon, Ethel Sherry; Samueloff, Arnon; Schimmel, Michael S.; Grisaru-Granovsky, Sorina
Abstract: Background: Preterm birth at very low birth weight (VLBW, < 1500 g) has a multitude of consequences that extend to various aspects of adult life. Little is known about the long-term reproductive outcome of VLBW that survive to adulthood. Aims: To evaluate the reproductive outcome of VLBW infants who survive to adulthood (next-generation). Study design: Retrospective cohort. Subjects: Infants born at a single tertiary center between the years 1982–1997 who survived to 18 years of age (first-generation). Outcome measures: The number and the birth weight of offspring from adults born with VLBW were compared to those of other birth weight groups born in the same epoch: 1500–2499 g, 2500–3799 g (reference group) and ≥ 3800 g. We calculated the ratio of actual compared to expected number of children in the next-generation for extreme birth weight parents, using the reference group as a control group and adjusting for birth year. Thereafter, we measured whether first-generation VLBW had an increased risk for a VLBW in the next-generation. Results: After exclusions, we identified first-generation 67, 183 births, including 618 (9.2%) VLBW. There were 193 males and 184 female VLBW infants who survived to adulthood. Both female and male first-generation patients from the VLBW group had half the reproductive rate relative for the normal birth weight group. After adjusting for parental age, male and female VLBW survivors had no significant risk for a VLBW neonate in the next-generation, however, the overall number of are small and may limit any conclusion. Conclusion: VLBW children who reach adulthood may be at a significantly lower reproductive capacity. Highlights: The reproductive rate of either females or males who are very low birth weight survivors is decreased by approximately 50%. Both males and females born at low birth weight who reach adulthood have a statistically significant lower reproductive capacity. Both males and females born at a high birth weight who reach adulthood have a statistically significant higher reproductive capacity.